Hepatitis B seroprotection in children aged 10-15 years after completion of basic hepatitis B immunizations - Novie Homenta Rampengan; Sri Rezeki Hadinegoro; Mulya Rahma Karyanti (Indonesian Pediatric Society Publishing House, 2017)
Background The prevalence of hepatitis B viral (HBV) infection in Indonesia is high. The most effective way to control HBV infection is by hepatitis B (HB) immunization. Many studies reported that hepatitis B surface antibody (anti-HBs) seroprotection declines in children > 10 years of age. In addition many factors can influence anti-HBs titer. Objective To measure anti-HBs titer and evaluate possible factors associated with anti-HBs titer. Methods This cross sectional  study was conducted in children 10-15 years of age from ten schools at Tuminting District, Manado, North Sulawesi, from October to November 2014. All subjects had completed the hepatitis B immunization scheme. By stratified random sampling, 105 children were selected as subjects. Data was analyzed with SPSS version 22. Results. From 48 schools, we selected 10 schools from which to draw a total of 105 children, but only 23 (21.9%) children had detectable anti-HBs . Of all subjects, 76 (72.4%)  were female, 78 (74.3%)  had good nutritional status, and 98 (93.3%)  had birth weight ≥2,500 grams. Data from immunization record books showed that 26 (24.8%) subjects received the HB-1 vaccination at ≤7 days of age and 45 (42.9%) subjects had a ≥2 month interval between the HB-2 and HB-3 vaccinations. Multivariate analysis showed that administration of HB-1 at ≤7 days of age  and a ≥2 month interval between HB-2 and HB-3  had significant associations with anti-HB seroprotection in children. Conclusion A low proportion of subjects who had completed the hepatitis B immunization scheme had detectable anti-HBs titer (21.9%). Administration of HB-1 at ≤7 days of age and a ≥2-month interval between HB-2 and HB-3 vaccinations are important factors in anti-HB seroprotection in children aged 10-15 years.